Therapeutic effects and safety of resveratrol for lung cancer: an updated preclinical systematic review and meta-analysis - Xiao, Xiang; Wu, Xuanyu; Li, Wenyuan; You, Fengming; Guo, Jing (Frontiers in Nutrition, 2025)
BackgroundLung cancer (LC) is the most common cause of cancer-related death worldwide, while there are limited treatment methods. Resveratrol (RESV), a natural food-derived compound, has attracted attention around the world for its anti-LC effects. However, little is known about the efficacy and safety of RESV for LC.PurposeThis study aimed to provide preclinical evidence for the efficacy and safety of RESV for LC, and to find the optimal dose and duration.MethodsIn vivo studies of RESV against LC, published before 24 July 2024, were retrieved from PubMed, Embase, Web of Science, and Cochrane Library. The CAMARADES checklist was used to assess study quality. Primary outcomes were tumor volume and tumor weight. Secondary outcomes included body weight, lung metastases number, and the apoptotic cell proportion. Statistical analysis was performed using RevMan 5.3 and Stata 16.0. Dose–duration–effect model was conducted to determine the optimal dose and duration, and the toxicology of RESV was predicted through the ProTox 3.0 platform.ResultsA total of 23 studies involving 425 animals were included. The methodological quality of included studies was medium-to-low. RESV significantly reduced tumor volume, tumor weight, and lung metastases number, and increased apoptotic cell proportion, while having no effect on body weight. High heterogeneity was observed, and subgroup analysis suggested that the heterogeneity was partly attributed to the dose of RESV. The optimal dose and duration of RESV were 30–100 mg/kg and 25–28 days, respectively. The median lethal dose of RESV was 1,560 mg/kg.ConclusionRESV demonstrated a significant inhibitory effect on LC in vivo. However, the lower research quality and high heterogeneity call for more high-quality preclinical studies to be conducted. Before achieving clinical translational research on RESV, the problem of low bioavailability of RESV needs to be solved.